The Essence of the Professional Self-Awareness of The Future Teacher - Chulpanova Hadicha Tashbayevna (Genius Journals, 2022)
Self-development of a person in professional activity and optimization of the training process can be considered in the context of subject -activity and system approaches. An integrated, systematic approach to training allows you to increase the activity, consciousness, responsibility of future specialists for their professional choice and self-realization in the profession. Psychological self-awareness in the upcoming professional activity can be considered as a necessary prerequisite for the formation of a specialist in a higher education institution, the increased quality and efficiency of his training
Keywords: self-knowledge; self-improvement; initiation and self-assessment